A Review of History, Definition, Classification, Source, Transmission, and Pathogenesis of Salmonella: A Model for Human Infection - Rahman, Heshu Sulaiman; Mahmoud, Bakhtyar Muhamad; Othman, Hemn Hassan; Amin, Kawa (Sulaimani Journal for Pure and Applied Sciences, 2018)
Salmonella is one of the most frequently isolated food-borne microorganism. It is a major world-wide public health involvement, accounting for 93.8 million food-borne illnesses and 155,000 deaths per year. The genus Salmonella is a member of the bacterial family Enterobacteriaceae named in recognition of a famous veterinary bacteriologist Daniel E. Salmon (1850 - 1914). The genus consists of more than 2500 serological distinguishable variants in which more than half of them belong to Salmonella enterica subsp. enterica, which accounts for the majority of Salmonella infections in humans. Most of Salmonella serotypes are potentially pathogenic, causing sporadic infections, as well as outbreaks of fatalities, while some are less pathogenic and causing minor infections in both human and most animal species. Preventive measures have been proposed to eliminate the spread of Salmonella infection. While the maintenance of effective food hygiene and water sanitation remain the cornerstones, additional measures such as restriction of indiscriminate use of antibiotics in food animals are important. The aim of this review is to highlight the history, bacterial definition, classification of its species, source of infection and contamination, transmission routes, and finally pathogenesis.
Keywords: Bacterial infection; zoonotic disease; food poisoning; contamination; review